Research on Hotel Green Management Model Based on Sustainable Development Strategy - Sun Langjing (SHS Web of Conferences)
Currently, the traditional hotel business model urgently needs to be transformed and upgraded. It should be combined with sustainable development strategies, integrate green development concepts, and create a hotel green management model based on sustainable development strategies. Meanwhile, scientifically improving the green management system of hotels cannot be achieved overnight. It requires the joint efforts of hotels and customers to fully implement the concept of green development. It can be said that implementing and improving the green management model of hotels, following the sustainable development strategy, not only requires the participation of hotel managers but also the cooperation of consumer groups. Therefore, this article explores the definitions of sustainable development strategy and hotel green management, emphasizes the significance of hotel green management model based on sustainable development strategy, and points out the basic principles of hotel green management model based on sustainable development strategy, including resource reduction principle, resource substitution principle, resource reuse principle, and resource recycling principle. It also points out the problems that hotels currently face in implementing a green management model and proposes targeted solutions.